2011
DOI: 10.1007/s11258-011-0009-x
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive characteristics of grassland community structure and leaf traits along an altitudinal gradient on a subtropical mountain in Chongqing, China

Abstract: Community structure and leaf traits are important elements of terrestrial ecosystems. Changes of community structure and leaf traits are of particular use in the study of the influence of climate change on terrestrial ecosystems. Patterns of community structure (including species richness, above-and belowground biomass) and leaf traits (including leaf mass per area (LMA), nitrogen content both on mass and area bases (N mass and N area ), and foliar d 13 C) from 19 grassland plots along an altitudinal transect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…3, 4). For instance, in the Montane Grassland biome in Chongqing, China (Song et al 2012) and in southern Norway (Guittar et al 2016), species with higher SLA are more abundant in warmer temperatures at lower elevations. However, in Montane Grasslands of North-western Caucasus in Russia (Soudzilovskaia et al 2013), species with lower SLA are more abundant in warmer climates.…”
Section: Specific Leaf Area (Sla)mentioning
confidence: 99%
“…3, 4). For instance, in the Montane Grassland biome in Chongqing, China (Song et al 2012) and in southern Norway (Guittar et al 2016), species with higher SLA are more abundant in warmer temperatures at lower elevations. However, in Montane Grasslands of North-western Caucasus in Russia (Soudzilovskaia et al 2013), species with lower SLA are more abundant in warmer climates.…”
Section: Specific Leaf Area (Sla)mentioning
confidence: 99%
“…Studies on deciduous forest and herbaceous species have shown an increase of leaf mass per area (LMA) and leaf nitrogen content per unit area with increasing altitude (Williams et al 1995, Song et al 2012. Other studies have reported increases in stomatal density, stomatal conductance, and light-saturated rate of CO 2 assimilation with increasing altitude (Hultine andMarshall 2000, Vats et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation is a key environmental factor that determines water availability in desert ecosystems and regulates the responses of plant communities and entire ecosystems [ 6 , 7 , 8 ]. The response and adaptation of desert plant community characteristics and their leaf stoichiometric traits to precipitation are of the utmost importance, as community characteristics and leaf traits are fundamental elements in understanding the structure and function of ecosystems [ 9 , 10 , 11 ]. Precipitation affects community characteristics and leaf traits in complex ways, especially in a changing climate.…”
Section: Introductionmentioning
confidence: 99%